(untitled) - Lumsden, Gay; Gay Lumsden; Donald Lumsden (Belmont, CA, 2004)
Emphasizing teamwork, leadership and technology, this text distinguishes itself in two major ways: its emphasis on teamwork and leadership skills and its integration of ethics and diversity throughout. This text is especially timely because of the recent attention given to teams in business and industry, the examination of technology's role in small group communication, and the growing awareness that colleges should be challenging students to examine their own leadership competence and understand the ethical and social implications of the groups in which they participate
Includes bibliographical references (p. 381-392) and indexes
Keywords: Communication in organizations; Teams in the workplace